The Implementation of One Opportunistic Routing in Wireless Networks - Han Li; Huan-yan Qian (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In the paper, it proposes an optimization framework addressing fairness issues for opportunity routing in wireless mesh networks, where we use network coding to ease the routing problem. We propose a distributed heuristic algorithm in the case when scheduling is determined by MAC, and discuss the suitability of our algorithm through simulations. It is found that in most situations our algorithm has better performances than the single-path algorithm and the classical network coding which is based opportunity algorithm MORE.